Hubungan Ketepatan Pemberian Makanan Pendamping Asi (Mpasi) Dengan Kejadian Stunting Pada Anak Usia 6-23 Bulan Di Wilayah Kerja Puskesmas Kota Ende Provinsi Nusa Tenggara Timur Tahun 2024 - Yustina Hendrayati Baba; Siti Soraya; Lulu’ul Badriyah (Program Studi Gizi UNSIKA, 2024)
Nutrition given from the moment the baby is born certainly has a big influence on growth, including the risk of stunting. This study aims to determine the relationship between the accuracy of providing complementary breast milk (MPASI) and the incidence of stunting in children aged 6-23 months. This research uses an analytical observational design with a case control approach. The research was conducted in January 2024 using a questionnaire and anthropometric measurements. The research population of mothers who had children aged 0-23 months in the stunting and non-stunting categories in the Ende City Health Center Working Area, East Nusa Tenggara Province was 62 samples. Data analysis was used to determine the relationship between the accuracy of providing complementary foods (MPASI) and the incidence of stunting in children aged 6-23 months. The measuring instrument used to measure the accuracy of providing complementary breast milk (MPASI) is referred to the MPASI Principles according to WHO (2003) and nutritional status parameters for measuring stunting use nutritional status parameters (2020). Based on the research results, it shows that the accuracy of providing complementary breast milk (MPASI) is related to the incidence of stunting in children aged 6-23 months. There is a significant relationship between the accuracy of providing MP-ASI, which includes the ingredients for making MPASI, the frequency of MPASI, and the number of MPASI portions and the incidence of stunting in children aged 6-23 monthsat the Ende City Health Center, East Nusa Tenggara Province. Keywords: stunting, complementary foods for breast milk